Integration between Akidah Akhlak Education and the Talqin Dhikr of the Qadiriyah Naqshabandiyah Suryalaya Sirnarasa Thariqah at Islamic Senior High Schools (Program Studi Pendidikan Agama Islam, 2025)
The purpose of this study is to understand how the integration between the education of the Moral Faith at Madrasah Aliyah and the talqin dhikr of Qadiriyah Naqshabandiyah Suryalaya Sirnarasa can create a positive synergy in efforts to shape students' worship behavior. This field research used qualitative method with a case study approach. The background of this research was Madrasah Aliyah Miftahus Shudur Pati. In-depth interviews with madrasah principals, talqin deputy teachers, and moral faith teachers served as primary sources, supported by secondary sources of the Mifathus Shudur Book. Observation and documentation complemented the data collection technique. Data analysis involved condensing data, displaying data, and drawing and verifying conclusions. The results of the study revealed that the integration between Akidah Akhlak education and talqin dhikr qadiriyah naqshabandiyah Suryalaya Sirnarasa was carried out by careful planning using a spiritual approach by carrying out daily amaliyah (daily dhikr), weekly amaliyah (khotaman), and monthly amaliyah (manakiban). The contribution of the research provides a new method in Islamic education in the form of integrating spirituality values in Islamic religious learning in formal schools.